Effect of Feeding Moringa (Moringa oleifera) as Green Fodder on Feed Intake, Milk Yield, Microbial Protein Synthesis and Blood Profile in Crossbred Cows - Shankhpal, Sachin; Waghela, Chanchal; Sherasia, Pankaj; Sridhar, V; Srivastava, A K; Singh, Digvijay (Indian Journal of Animal Nutrition, 2019)
To evaluate the effect of feeding Moringa (Moringa oleifera) as green fodder on feed intake, milk yield, microbial protein synthesis, and blood profile, a study was conducted on twenty lactating crossbred cows in Anand district of Gujarat. Cows were divided into two groups of ten each, based on milk yield (9-10 kg/d), fat (3.5-3.8%) and stage of lactation (30-100 days in milk). Cows in control group were fed 3.0 kg each chaffed wheat and pulse straw, 15.0 kg green hybrid napier and 5.0 kg cattle feed (23.0% CP; 4.0% EE). Whereas, cows in experimental group were fed 15.0 kg Moringa green fodder (by replacing 15.0 kg hybrid napier) for 90 days. Nutrient requirement was adjusted by reducing quantity of cattle feed (3.5 kg). Study revealed that milk yield and fat percent increased (P<0.01) by 9.17% and 7.41%, respectively in experimental group, as compared to control group. Level of Î²-carotene improved by 37.76%, while level of cholesterol decreased by 17.60% in cows fed Moringa as green fodder. Feeding of Moringa fodder improved intestinal flow of microbial nitrogen from 112.67 to 159.53 g/d (P<0.01). Serum non-esterified fatty acid (NEFA) reduced from 0.28 to 0.22 meq/L (P<0.05) whereas, serum ferric antioxidant power (FRAP) increased from 442.73 to 849.44 (P<0.01) in experimental group. Level of serum immunoglobulin IgM was higher by 22.19% (P<0.05) in experimental cows. Organoleptic properties of milk were not affected by feeding Moringa green fodder in the ration of dairy cows. The average net daily income was higher by Rs. 46.21 (P<0.01) by replacing hybrid napier with Moringa fodder. Study concludes that feeding Moringa oleifera is highly nutritious fodder, and palatable; thus can be used as green fodder for lactating cows under field conditions.